Migratory Transient Osteoporosis of Foot and Ankle: A Rare Cause of Foot and Ankle Pain - Lakhey, Shishir; Jha, Daman Kumar (Nepal Orthopaedic Association Journal, 2025)
BACKGROUNDWe describe a bone marrow edema (BME) involving the talus, which kept shifting to other tarsal bones. A 55-year-old female presented with pain in the right ankle without any history of trauma. The symptoms did not improve, and the initial MRI showed bone marrow edema involving the talar head, which later shifted consecutively to the cuboid, fifth metatarsal, and talar dome. We managed this case with protected weight bearing, analgesics, vitamin D, Calcium, and Alendronate. She was completely symptom-free at 11 months of follow-up.